2012
DOI: 10.1186/1756-8935-5-13
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin is required for expression of the estrogen receptor-alpha (ESR1) gene

Abstract: BackgroundIn conjunction with posttranslational chromatin modifications, proper arrangement of higher order chromatin structure appears to be important for controlling transcription in the nucleus. Recent genome-wide studies have shown that the Estrogen Receptor-alpha (ERα), encoded by the ESR1 gene, nucleates tissue-specific long-range chromosomal interactions in collaboration with the cohesin complex. Furthermore, the Mediator complex not only regulates ERα activity, but also interacts with the cohesin compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…This is consistent with findings by Prenzel et al ,5 where ERα expression was impaired when MED12 was knocked down in breast cancer cell lines. However, in the stromal component, we observed no ERα expression in all cases except for the single fibroadenoma with smooth muscle metaplasia, even if the tumours expressed MED12 protein.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with findings by Prenzel et al ,5 where ERα expression was impaired when MED12 was knocked down in breast cancer cell lines. However, in the stromal component, we observed no ERα expression in all cases except for the single fibroadenoma with smooth muscle metaplasia, even if the tumours expressed MED12 protein.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, the mediator complex is also an essential coactivator for a broad range of nuclear hormone receptors 4. Prenzel et al 5 reported a decrease in oestrogen receptor α (ERα) protein levels and a significant impairment to oestrogen-regulated transcriptome following knockdown of the MED12 gene in MCF7 breast cancer cell lines 5. Kang et al 6 demonstrated that the mediator complex interacts directly with ERα and ERβ and enhances receptor function in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that MED12 colocalizes on the ERα ( ESR1 ) gene with the cohesion subunit SMC3. The occupancy of either subunit across the ESR1 gene depends on the other, and both are required for RNAPII–mediated transcriptional initiation, suggesting that high‐order chromatin architecture controlled by MED12 and cohesin may be exploited for the regulation of ER expression and the treatment of estrogen‐dependent breast cancer . However, control of ER expression and ER‐regulated transcription in ER‐driven malignancies is far more complex and has been elegantly reviewed by others .…”
Section: The Relevance Of Med12 To the Estrogen Pathwaymentioning
confidence: 99%
“…The occupancy of either subunit across the ESR1 gene depends on the other, and both are required for RNAPII-mediated transcriptional initiation, suggesting that high-order chromatin architecture controlled by MED12 and cohesin may be exploited for the regulation of ER expression and the treatment of estrogen-dependent breast cancer. 48 However, control of ER expression and ER-regulated transcription in ER-driven malignancies is far more complex and has been elegantly reviewed by others. 49,50 Liu and colleagues recently reported that MED12 interacts with the JmjC-domaincontaining protein (JMJD6) and recruits JMJD6 to the active enhancers bound by ERα, releasing paused RNA polymerase on cognate estrogen target genes.…”
Section: The Relevance Of Med12 To the Estrogen Pathwaymentioning
confidence: 99%
“…For example, loss-of-function approach coupled with gene expression microarray profiling demonstrated that BRD4, KDM3A, and Cohesin are required for the expression of a large portion of ERα target genes [18, 4042]. GATA3 and FOXA1 have been implied as the pioneer factors for priming the genome-wide distribution of ERα [36, 39].…”
Section: Discussionmentioning
confidence: 99%